Advancing Capsule Technology: A Comprehensive Review of Formulation Strategies - Mohd. Wasiullah; Piyush Yadav; Shashikant Maury; Mohammad Aquif Sheikh (International Journal of Antibiotics, 2025)
Capsules are a popular and versatile oral dosage form used in drug delivery, offering benefits such as ease of swallowing, taste masking, and improved stability of active pharmaceutical ingredients (APIs). They can be made from gelatin or non-gelatin materials like Hydroxypropyl Methylcellulose (HPMC), Polyvinyl Alcohol (PVA), and starch, catering to dietary, cultural, and sustainability needs. Capsules can be engineered for controlled, sustained, or targeted release, enhancing bioavailability, particularly for poorly soluble drugs. They can hold powders, granules, liquids, and even combination therapies, offering flexibility in drug formulation and delivery. The manufacturing process of capsules involves precision, with hard gelatin capsules produced using the dip-coating method, and soft gelatin capsules made via plate, rotary die, or seamless techniques. Strict quality control ensures the capsules meet standards for weight, content uniformity, and disintegration. Non-gelatin capsules also cater to specific needs, offering plant-based or eco-friendly alternatives without compromising on drug delivery. Technological advancements in capsule manufacturing, such as controlled release, biodegradable materials, and 3D printing, are improving patient compliance and therapeutic outcomes. Capsules remain a vital and adaptable tool in modern drug delivery systems, offering solutions for a wide range of therapeutic applications.
Keywords: Capsules; Formulation; Quality control tests; gelatin; manufacturing